IMPLEMENTATION OF THE INDEPENDENT VILLAGE PROGRAM POLICY IN COMMUNITY ECONOMIC EMPOWERMENT IN SEKADAU HILIR DISTRICT, SEKADAU REGENCY - Kornelia Meilinda Betsyeba; Martoyo; Herlan (RADJA PUBLIKA, 2025)
The title of this study is